EFFECT OF AGE ON POSTNATAL DEVELOPMENT OF BODY WEIGHT AND SCROTAL CIRCUMFERENCE IN ASSAM GOAT (CAPRA HIRCUS)
The present study was conducted on thirty Assam local goats divided into six age groups viz. group-I "(O" day), group-II (2 months), group-Ill (4 months), group-IV ( 6 months), group-V (8 months) and group-VI (10 months) consisting of five animals in each group. The mean body weight of the male kids ranged from 0.85 ± 0.03 kg at birth (group-I